Supermode Characteristics of Nested Multiple Hollow-Core Anti-Resonant Fibers - Zequan Li; Jiantao Liu; Changming Xia; Zhiyun Hou; Guiyao Zhou (Photonics, 2022)
Mode-division multiplexing (MDM) can achieve ultra-high data capacity in optical fiber communication. Several impressive works on multicore fiber (MCF), multi-mode fiber, and few-mode multicore fiber have made significant achievements in MDM. However, none of the previous works can simultaneously maintain the transmission loss, chromatic dispersion (CD), and differential group delay (DGD) at a relatively low level. A nested multiple hollow-core anti-resonant fiber (NMH-ARF) has significant potential for applications in MDM. This study proposes a novel NMH-ARF with its structural design based on the traditional single-core nested anti-resonant fiber. We increased the number of nodes between capillaries. By changing the position of the nested tubes, several interconnected areas form when a single core is separated. We investigated the mode-coupling theory and transmission characteristics of this fiber. This fiber structure showed a low sensitivity to bending and achieved a super-low DGD and a super-low confinement loss (CL) at a wavelength of 1.55 µm while keeping CD relatively low.